Work rate adjustments needed to maintain heart rate and RPE during high-intensity interval training in the heat - Yoder, Hillary A.; Mulholland, Anne M.; MacDonald, Hayley V.; Wingo, Jonathan E. (Frontiers in Physiology, 2025)
IntroductionHigher work rates may be sustainable when maintaining target rating of perceived exertion (RPE) compared to maintaining target heart rate (THR) during high-intensity interval training (HIIT) exercise in hot conditions, but may also result in greater thermal strain and cardiovascular drift, as well as greater decrements in maximal oxygen uptake (V˙O2max).PurposeTo test the hypotheses that maintaining target RPE compared to THR during HIIT in the heat results in 1) smaller work rate adjustments, 2) greater thermal and cardiovascular strain, and 3) larger decreases in V˙O2max.MethodsEight adults (4 women) completed a graded exercise test on a cycle ergometer in 22°C and then 4 cycling trials in 35°C, consisting of an 8-min warm-up at 70% maximal heart rate (HRmax) or 12 RPE followed by 1 (15HR and 15RPE) or 5 (43HR and 43RPE) rounds of HIIT (1 round = 4 min work at 90% HRmax or 17 RPE and 3 min recovery at 70% HRmax or 12 RPE) totaling 15 min or 43 min of exercise, respectively. Each trial ended with a GXT to measure V˙O2max.ResultsIn the 43-min trials work rate decreased from the first to the fifth work interval in both conditions, but by a non-significant, yet moderately larger (ES = 0.53) amount during 43HR (46 ± 29 W) compared to 43RPE (30 ± 28 W). From the first to fifth work interval HR increased over time by 12 b⋅min–1 in 43RPE (p < 0.001), but did not increase during 43HR (p = 0.36). Rectal temperature increases were not different between conditions (43HR = 0.7°C, p < 0.001; 43RPE = 0.8°C, p < 0.001). V˙O2max decreased 15.6% (ES = 0.41) between 15RPE and 43RPE (p = 0.005), but it was not different over time during the HR-based trials [6.5%, ES = 0.16 (α adjusted for multiple comparisons = 0.0125) p = 0.03].ConclusionMaintaining target RPE and THR require considerable declines in work rate during HIIT in the heat, with ∼53% larger declines needed to maintain THR. The mitigation of cardiovascular drift in the THR trial may have contributed to the preservation of V˙O2max.